2019
DOI: 10.1021/acsaelm.9b00057
|View full text |Cite
|
Sign up to set email alerts
|

Local Modulation of Electrical Transport in 2D Layered Materials Induced by Electron Beam Irradiation

Abstract: Effective doping techniques that precisely and locally control the conductivity and carrier polarity, i.e., electron (n-type) or hole (p-type), play a vital role in the remarkable success of Si-based technology and thus are critical for developing useful devices based on two-dimensional layered transition-metal dichalcogenides (TMDs). In contrast to the previous approaches based on either chemical doping or phase transition that requires complex chemicals or a high thermal budget and shows limited tunability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…Moreover, it has also been reported that the band gap as well as the conductivity of the chalcogenides can be modulated using electron beam irradiation, which may also play an important role in the formation of favorable chalcogenide/p-Si heterojunction for the photovoltaic (PV) applications. 58 2.7.1. Thickness-and Doping Concentration-Dependent PV Performance.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has also been reported that the band gap as well as the conductivity of the chalcogenides can be modulated using electron beam irradiation, which may also play an important role in the formation of favorable chalcogenide/p-Si heterojunction for the photovoltaic (PV) applications. 58 2.7.1. Thickness-and Doping Concentration-Dependent PV Performance.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be attributed to the defect states induced by the S-vacancies, which may shift the Fermi level toward the conduction band edge, resulting in metallic-like behavior. 35,36 Accordingly, Fig. 3d–f display the corresponding I d – V g characteristics, respectively, where the NDR effect can be seen clearly in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Some defects with relatively shallow energy levels would lead to the change of carrier distribution and eventually regulate conduction properties [63][64][65]. Thus, TMDCs could be intrinsically doped by the controllable intrinsic defect engineering, which has the advantages of easy patterning without any implanting impurity [66][67][68]. When synthesizing TMDCs, the defect tailoring and doping effect level could be in-situ modulated by stoichiometric ratio [67,69].…”
Section: Intrinsic Defect Tailoringmentioning
confidence: 99%
“…The high Se/Pt ratio was realized by a slow cool down process with a continuous supply of Se precursor, while the low Se/Pt ratio was achieved by a rapid cool down process followed by Se precursor removal. Besides the in-situ growth presented above, the defects could be also created by post-growth approaches, that all have the advantage of patterned doping capability, for instance, chemical treatment [66], plasma or electron beam etching [68,70,71], and light illumination [72]. A great example of chemical treatment for the intrinsic defect tailoring of MoS2 is presented in Fig.…”
Section: Intrinsic Defect Tailoringmentioning
confidence: 99%